Counting Fluorescent dye molecules on DNA origami by means of photon statistics - Kurz, Anton; Schmied, Jürgen J.; Grußmayer, Kristin Stefanie; Holzmeister, Phil; Tinnefeld, Philip; Herten, Dirk-Peter (Small, 2013)
Obtaining quantitative information about molecular assemblies with high spatial and temporal resolution is a challenging task in fluorescence microscopy. Single-molecule techniques build on the ability to count molecules one by one. Here, a method is presented that extends recent approaches to analyze the statistics of coincidently emitted photons to enable reliable counting of molecules in the range of 1-20. This method does not require photochemistry such as blinking or bleaching. DNA origami structures are labeled with up to 36 dye molecules as a new evaluation tool to characterize this counting by a photon statistics approach. Labeled DNA origami has a well-defined labeling stoichiometry and ensures equal brightness for all dyes incorporated. Bias and precision of the estimating algorithm are determined, along with the minimal acquisition time required for robust estimation. Complexes containing up to 18 molecules can be investigated non-invasively within 150 ms. The method might become a quantifying add-on for confocal microscopes and could be especially powerful in combination with STED/RESOLFT-type microscopy.
Gesehen am 22.07.2021